A Comparative Study of Turkish and Spanish Translations of The Crucible - González Vera, María Pilar; Tilfarlioglu, Filiz Yalcin (Íkala, Revista de Lenguaje y Cultura, 2008)
This text demonstrates how power and gender relationships affect the translation process of a literary text. More specifically, we will focus on the translation of linguistic politeness and politic behavior in Arthur Miller's The Crucible. While there is only one Turkish translation (1962) of the play, for the analysis of the Spanish translations we have chosen two from different eras, one from 1955 and another from 1997, with the intention of demonstrating how these translations have become a reflection of the socio-cultural situation of the target country at the moment they were written. Received: 04-10-2007 / Accepted: 04-08-2008 How to reference this article: Gonzalez Vera, P. & Yalcin Tilfarlioglu, F. (2008). Estudio comparativo de las traducciones al turco y al español de Las Brujas de Salem. Íkala. 13(2), pp.31-54